Estimation of shelf life of nutri noodles and butter gro-cookies - Tantengco, Ma. Lourdes T.; Alabastro, Estrella F. (1980.)
The study conducted with the main objective of determining the proper packaging of two selected nutri-foods, namely, Nutri-noodles and butter Gro cookies. The sorption isotherm of both products which were determined using the Winks weight equilibrium method, exhibited typical sigmoidal curves. The critical moisture contents were found to be 10.13% and 12.74% for Nutri-noodles and butte Gro cookies, respectively. Based on the soprtion isotherm and critical point, the maximum allowable WVTR requirement for a packaging materials was calculated to be 2.5887 g/M^2/day and 2.7643 g?m^2/day for Nutri-noodles and butter Gro cookies, respectively, at 90% RH gradient at 28°C to 30 °C. For both products, the same four packaging materials were selected based on their WVTR values and costs, namely: Saran coated cellophane (34.1 g/m^2), Nitro-cellulose coated cellophane (33.7 g/m^2), Cello/polyethylene (72.8 g/m^2), and Cello/PE/foil/PE (93.2 g//m^2). To assess the adequacy of the present packaging materials, Saran coated cellophane (306 g/m^2) for Nutri-noodles and Polypropylene (63.5 g/m^2) for butter Gro cookies were also tested. Shelf life of the products in sealed bags made of the above mentioned packaging materials were determined using the half-value period. Results showed that for both products, all packaging materials except Nitro-cellulose coated cellophane, were found to be adequate in attaining a targeted shelf-life of at least 3 months under average ambient conditions in the Philippines. These included the present packaging of both products which gave shelf life values of 111 days for Nutri-noodles and 103 days for butter Gro cookies.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Food -- Shelf-life dating